1976
DOI: 10.1128/jvi.18.2.644-651.1976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-deoxyglucose, glucosamine, and mannose on cell fusion and the glycoproteins of herpes simplex virus

Abstract: 2-Deoxyglucose and glucosamine were found to inhibit cell fusion caused by a syncytial mutant of herpes simplex virus and to inhibit the glycosylation of viral glycoproteins in the infected cells. The inhibition of fusion and the inhibition of glycosylation caused by 2-deoxyglucose were substantially prevented when mannose was also present during infection. When glycosylation was inhibited, three new bands were found in the major glycoprotein region on sodium dodecyl sulfate-polyacrylamide gels. These bands ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 24 publications
(36 reference statements)
8
34
0
Order By: Relevance
“…Mannose, as well as glucose, was found by MacDonald to reverse the 2-deoxy-D-glucose block of T-cell-mediated cytolysis (6). It has been shown that 2-deoxy-D-glucose interferes with virus-induced cell fusion (39). This effect is also reversed by mannose and glucose.…”
Section: Discussionmentioning
confidence: 98%
“…Mannose, as well as glucose, was found by MacDonald to reverse the 2-deoxy-D-glucose block of T-cell-mediated cytolysis (6). It has been shown that 2-deoxy-D-glucose interferes with virus-induced cell fusion (39). This effect is also reversed by mannose and glucose.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, synthesis, transport to intraceUular localization of virus budding, and proper function of the viral cell-attachment component appear not to be dependent on presence of Nlinked oligosaccharides. In contrast, the fusion activity of HSV glycoproteins must be abolished by the absence of N-linked oligosaccharides (Knowles and Person, 1976).…”
Section: Herpes Simplex Virusmentioning
confidence: 97%
“…This finding may rule out a nonspecific antiviral effect of GN, because a viral-induced cytopathogenic effect is still able to develop after a well defined period of incubation. In the case of enveloped viruses the inhibition of the cytopathogenic effect caused by G N could be explained, as currently suggested, by an impairment of the synthesis of the envelope glycoproteins (Scholtissek 1975;Kaluza 1975;Knowles & Person 1976). In the case of adenovirus, which is not an enveloped virus, it may be argued that GN may impair the synthesis of the capsidial glycoprotein.…”
Section: Discussionmentioning
confidence: 92%